PERKOSAAN, DAMPAK, DAN ALTERNATIF PENYEMBUHANNYA - - Ekandari; - Mustaqfirin; - Faturochman (Jurnal Psikologi, 2001)
Rape as a criminal behavior has continued and many victims suffered physical, psychological, and social problems. Among other problems, post traumatic stress disorder is a psychological problem found in four cases of rape in this study. Since there is no systematic social and structural solution to help the victims, family supports become the most possible treatment to lessen the psychological and social problems after experiencing those horrible events. Keywords: Rape, Solution.